Microstructural impact on electromigration reliability of gold interconnects. (February 2023) - Ceric, H.; de Orio, R.L.; Selberherr, S.
Abstract: Interconnect segments of gold metallization used for GaAs devices are susceptible to significant electromigration degradation and have a microstructure with thousands of grains. In this work, a complete physics-based analysis of electromigration in gold is presented. A novel approach for the numerically efficient simulation of an interconnect containing a large number of grains is introduced. By building grain compounds containing hundreds of grains and equipping them with appropriate models, the dependence of statistical failure features on the variation of geometric properties is investigated. The experimentally observed dependence of the mean failure time and the associated standard deviation of the failure times on the interconnect geometry is well reproduced by our simulations. Highlights: Numerical generation of artificial metal microstructures according to the statistical properties of real microstructures. Development of a numerically efficient methodology to model the effects of the microstructure of interconnect metals on their EM reliability. Explanation of EM failure behavior of gold interconnects and the role of microstructure.